PENINGKATAN HASIL BELAJAR OPERASI HITUNG CAMPURAN DENGAN PENDIDIKAN MATEMATIKA REALISTIK (PMR) - Turrahmi, Fauziah; Ariani, Yetti; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The research was conducted as study of Math that teacher centered where the teacher was not giving the opportunity for the students to play a role during the learning process.The purpose of this study to implementof Math by using PMR. The aim of this research was to describe the plan, the implementation of the plan, and the students’ learning achievement of Math by using PMR. The result of the research indicated that from the first cycle to the second one, the score of the Lesson Plan improved from 77 into 93, the teacher’s aspect improved from 73 into 90 and the students’ aspect improved from 75 into 90. Further, the students’ learning achievement improved from 37,5 into 87,5 Thus, the use PMR could improve the students’ learning achievement.